Chemotaxonomic Markers for the Leaf Buds of Common Finnish Trees and Shrubs: A Rapid UHPLC MS Fingerprinting Tool for Species Identification - Manninen Marianna; Karonen Maarit; Salminen Juha-Pekka (MDPI, 2022)
In this study, a chemotaxonomic tool was created on the basis of ultra-high-performance liquid chromatography-mass spectrometry (UHPLC-MS) for the identification of 13 common Finnish deciduous trees and shrubs from their leaf bud metabolites. The bud extracts were screened with UHPLC-ESI-QqQ-MS and UHPLC-ESI-Q-Orbitrap-MS to discover suitable markers for each species. Two approaches were tested in the marker selection: (1) unique species-specific markers to obtain selective fingerprints per species and (2) major markers to maximise the sensitivity of the fingerprints. The markers were used to create two selected ion-recording-based fingerprinting tools with UHPLC-ESI-QqQ-MS. The methods were evaluated for their selectivity, repeatability, and robustness in plant species identification by analysing leaf buds from several replicates of each species. The created chemotaxonomic tools were shown to provide unique chromatographic profiles for the studied species in less than 6 min. A variety of plant metabolites, such as flavonoids, triterpenoids, and hydroxycinnamic acid derivatives, were found to serve as good chemotaxonomic markers for the studied species. In 10 out of 13 cases, species-specific markers were superior in creating selective and repeatable fingerprints.